Fabrication of Glycerin-Based Chest Phantom as a Simulation Model for Paediatric Pneumonia - Khoiru Ainin Nisa,; Choirul Anam,; Ilham Alkian,; Arij Naufal,; Heri Sutanto, (International Journal of Scientific Research in Science and Technology, 2025)
This study aims to fabricate a chest phantom that can replicate pneumonia cases in patients using materials that are easily found in the market. The materials used were polymethyl methacrylate (PMMA), polyurethane (PU) foam, and calcium carbonate which each replace the patient's soft tissue, lungs, and ribs, respectively. The patient's pneumonia case was replicated using glycerin fluid. The fabricated phantom was scanned using a GE Revolution EVO 128 slice CT scanner with a tube current of 100 mA and tube voltages of 80, 100, 120 and 140 kV. Image analysis was performed by comparing phantom images with patient images exposed using the same exposure factor. The parameters of CT number, signal-to-noise ratio (SNR), and contrast-to-noise ratio (CNR) were used to compared images of the fabricated phantom and patients. The results showed that the CT numbers produced by soft tissue, bone, and normal lungs in the fabricated phantom were in the range of CT numbers of soft tissue, bone, and normal lungs in the patient image. Meanwhile, the CT number of pneumonia in the phantom (-805 HU) was still different from the CT number of pneumonia in the patient image (-57 to 49 HU). It can be concluded that the fabricated phantom has succeeded in replicating the main anatomical features of the patient (normal soft tissue, bone, and lung). However, replication of pneumonia needs to be improved so that it will be similar to the real case of pneumonia.
Keywords: Pneumonia; Chest Phantom; CT Thorax; Radiodiagnostics; Image Quality